Testing the one-part fractional response model against an alternative two-part model - Harald Oberhofer; Michael Pfaffermayr (University of Salzburg, Department of Social Sciences and Economics, 2011)
This note proposes a generalized two-part model for fractional response variables that nests the one-part model proposed by Papke and Wooldridge (1996). Consequently, a Wald test allows to discriminate between these two competing models. A small scale Monte Carlo simulation demonstrates that the proposed Wald test is properly sized and equipped with higher power than an alternative non-nested P-test.
Keywords: C12; C15; C21; C25; 330; Fractional response models; two-part model; Wald test; P-test